2017
DOI: 10.1177/0047287517734943
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Economic Globalization: An Emerging Research Agenda

Abstract: Globalization characterizes the economic, social, political, and cultural spheres of the modern world. Tourism has long been claimed as a crucial force shaping globalization, while in turn the developments of the tourism sector are under the influences of growing interdependence across the world. As globalization proceeds, destination countries have become more and more susceptible to local and global events. By linking the existing literature coherently, this study explores a number of themes on economic glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 78 publications
2
63
0
2
Order By: Relevance
“…Balli et al (2019) also examined the relationship between tourism and CO 2 emissions, and their findings provide that tourism raises the level of CO 2 emissions. Through the qualitative study of Song et al (2018), research has established that there is a connection between tourism and economic globalization. Another study by Javid and Katircioglu (2017) found that social economic and political globalization played a major role in the influence of tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Balli et al (2019) also examined the relationship between tourism and CO 2 emissions, and their findings provide that tourism raises the level of CO 2 emissions. Through the qualitative study of Song et al (2018), research has established that there is a connection between tourism and economic globalization. Another study by Javid and Katircioglu (2017) found that social economic and political globalization played a major role in the influence of tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the late 1980s, sustainable development has been at the heart of the development of societies (Liu, 2003). This concern over time coincided with the exponential growth of worldwide tourist flows, which by the end of the 1990s already represented about 674 million international tourist arrivals in the world according to Song, Li & Cao (2018) citing data from the World Tourism Organization.…”
Section: Sustainable Development and Sportsmentioning
confidence: 99%
“…Parafrazirajući Stiglitza (2002), promatrano s ekonomskog aspekta razvoja, turizam je i proces i posljedica ekonomske globalizacije. Song et al (2017) ističu da je globalizacija izravna posljedica pojačane konkurencije na tržištu.…”
Section: Strukturne Promjene Na Europskom Turističkom Tržištuunclassified